The Effect of Physical Welfare on Physical Activity of the Elderly - Risna Syarifuddin; Kartika (Science Midwifery, 2022)
Healthy individuals are able to perform daily activities independently. Whereas in the elderly, diseases that attack can make the elderly experience dependence either at mild, moderate or severe levels. This study aims to determine the effect of physical well-being on the physical activity of the elderly in Lampeudeu Tunong Village, Pidie District, Pidie Regency. This research is analytic with cross-sectional approach. The population in this study were all elderly people who live in Lampeudeu Tunong Village, Pidie District, Pidie Regency, namely 35 people. This research was conducted from 21 to 23 September 2021. Based on the results of research and discussion, it can be concluded that the majority of respondents have moderate physical activity, namely 22 respondents (62.9%), the majority of respondents have poor physical well-being, as many as 23 respondents (65.7%) and there is an effect of physical well-being on the physical activity of the elderly in Lampeudeu Tunong Village, Pidie District, Pidie Regency (p value = 0.028 0.05). It is suggested to respondents to be able to maintain their health and also keep active, even if it is a light activity considering that physical activity can maintain body fitness.